EFEKTIFITAS METODE FERNALD DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN BAGI ANAK KESULITAN BELAJAR - Yola Putri (Universitas Negeri Padang, 2014)
Abstrack: This research was motivated by the problems that researchers found in a child's learning difficulties in class III SDN 09 Sarilamak Payakumbuh . Supposedly these students are proficient in reading or writing , but after I invent a test he is not yet able to read the word , from the test results that I did to read the words ( 10 nouns ) often occurs phoneme or word replacement ( substitution ) for example the word closet lemati read , read Kusi seat .. This study used the approach in the form of single- subject experimental research ( study a single subject ) , by using design A - B - A , and data analysis techniques using visual analysis chart . Subjects were children trouble learning to read . Assessment in this study is to measure the percentage of students' skills in beginning reading ( reading noun) . Based on the results of the study shows that the ability of children's learning difficulties in reading the beginning (noun ) can be enhanced through the method of Fernald . In the baseline condition ( A1 ) is performed five times a meeting , 2 children can read a given noun that percentage is 20 % . In the intervention condition ( B ) is done as much as 7 times and meeting the child 's ability to learn increases the difficulty of meeting up to six to twelve with a highest score of 100 % to read the beginning (noun ) , whereas in the baseline condition ( A2 ) conducted five meetings and the child's score is the highest is 100 % to read the beginning (noun ) . Thus the hypothesis ( Ha ) proposed is acceptable . This means Fernald effective method to improve reading skills beginning (noun ) the child's learning difficulties in SDN 09 Sarilamak Payakumbuh . It can be concluded that the Fernald method is effective for improving reading skills beginning (noun ) the child's learning difficulties . Researchers suggest teachers should use the Fernald method to help improve reading skills in children who learning disabilities . Kata kunci: Kesulitan Belajar; Kemampuan Membaca Kata; Metode Fernald.